Study of burnt rice husk performance in reedbeds to remove pollutant form landfill leachate - Nurul Anati, Ariffin (2010)
In this study, the raw material used to treat the leachate is rice husks. Analyses were done on their physical and optical parameters to determine the removal and reduction of heavy metals (iron, chromium and nickel), BOD 5, COD, ammonia nitrogen, turbidity, colour and odour in leachate using biological treatment. For the physical, the testing was running to examine the performance of reedbed to improve landfill leachate. While for the optical parameter, scanning electron microscope (SEM) was used to investigate their morphological structures to determine the effect of burnt rice husk sizes and porosity on pollutant removal. At the end of the study, those criteria were exhibited from testing results, the treatment of leachate in reedbeds effective until four days and this reedbeds can be commercialized. Besides that, the raw materials used can be abundantly earned without cost, which in turn reduce the cost of production. Moreover, by this way, it can reduce the sludge disposal, which make it highly valuable in terms of environmental, and market value.